The assamiids harvestmen (Opiliones: Laniatores: Assamiidae) from Champasak Province, Laos - Zhang, Chao; Zhang, Feng (Zootaxa, 2015)
Three assamiids species are recorded from southern Laos, two of which are new: Paramaracandus dolabratus sp. nov. (male) and Simalurius suzukii sp. nov. (male and female). Mysorea thaiensis Suzuki, 1985, that was previously known only from the type locality in northern Thailand is redescribed here. The family Assamiidae was first recorded from Laos.